Pengembangan Pola Kemitraan Kewirausahaan berbasis Syariah di Pondok Pesantren Al-Faruqi Pekanbaru, Riau - Ernita, Mahdar; Kusnadi, Kusnadi; Nurnasrina, Nurnasrina; Wulandari, Shevia (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2025)
This study was purposed to determine the development of sharia-based partnership patterns at the Al Faruqi Islamic Boarding School in Pekanbaru. This study uses a descriptive qualitative method with samples of Entrepreneurship teachers and principals at Al-Faruqi Vocational School. This study concludes that there are 4 partners of the Al-Faruqi Islamic boarding school, namely the Ministry of Education and Culture of the Republic of Indonesia with a socio-religious pattern that provides grants for the construction of learning buildings and laboratories, then partnering with the Riau BI Representative with a socio-religious partnership pattern providing grants in the form of complete production facilities and infrastructure for cooking cakes and bakery as well as food and beverages to the halal certification process for each product, other assistance facilities are equipment to support fashion production. The social assistance provided by BI is carried out sustainably because the Al-Faruqi Islamic boarding school is able to process according to expectations and establish good relations.